2018
DOI: 10.1103/physreve.98.042146
|View full text |Cite
|
Sign up to set email alerts
|

Boundary conditions and the residual entropy of ice systems

Abstract: In this work we address the classical statistical mechanical problem of calculating the residual entropy of ice models. The numerical work found in the literature is usually based on extrapolating to infinite-size results obtained for finite-size systems with periodic boundary conditions. In this work we investigate how boundary conditions affect the calculation of the residual entropy for square, cubic, and hexagonal lattices using periodic, antiperiodic, and open boundary conditions. We show that periodic bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…Most of these rely on either enhanced sampling techniques or thermodynamic integration, giving good agreement with both experimental and theoretical values of the entropy. [23][24][25][26][27] To the best of our knowledge, the current computational literature surrounding ice/ammonium/feldspar interaction is limited, and generally focused on the dynamics of the surface interactions. Kumar et al found evidence for the adsorption of ammonium onto feldspar surfaces, although with different strengths depending on the geometry of the exposed plane.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these rely on either enhanced sampling techniques or thermodynamic integration, giving good agreement with both experimental and theoretical values of the entropy. [23][24][25][26][27] To the best of our knowledge, the current computational literature surrounding ice/ammonium/feldspar interaction is limited, and generally focused on the dynamics of the surface interactions. Kumar et al found evidence for the adsorption of ammonium onto feldspar surfaces, although with different strengths depending on the geometry of the exposed plane.…”
Section: Introductionmentioning
confidence: 99%
“…As for computational simulations, two simulation models (2-state model and 6-state model), which satisfied the ice rules in the ground state, were proposed and the value was estimated [6][7][8][9] by the Multicanonical (MUCA) Monte Carlo (MC) Method [10,11] (for reviews, see, e.g., [12,13]). After these simulation models were suggested, many research groups estimated the residual entropy by various computational approaches for the last decade (see, e.g., [14][15][16][17][18]). The estimates by computer simulations seem to be equal to or more accurate than theoretical estimate by Nagle.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of computer science, many research groups have tried to estimate the residual entropy by various computational approach (for example, Thermodynamic Integration method, Wang-Landau algorithm, and PEPS algorithm) [14][15][16][17][18]. However, there remain small differences between these results.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the actual structure of ice Ih and using a more rigorous approach, the Pauling expression has been corrected to R ln(1.507) = 3.40 J K/mol. 32 35 In spite of neglecting long-range effects such as ring closures, the Pauling approach is accurate to better than 1% for all ice structures. This accuracy is much better than the chemical accuracy aimed for here.…”
mentioning
confidence: 99%
“…This expression is based on the number of microstates allowed according to the Bernal-Fowler ice rules, where only one central water molecule and four tetrahedrally connected water molecules are considered. Considering the actual structure of ice Ih and using a more rigorous approach, the Pauling expression has been corrected to R ln­(1.507) = 3.40 J K/mol. In spite of neglecting long-range effects such as ring closures, the Pauling approach is accurate to better than 1% for all ice structures. This accuracy is much better than the chemical accuracy aimed for here. We note that Δ H ( T = 0 K) = Δ H ̃( T = 0 K) = Δ E lat ZPE ; that is, eqs , (), and () are identical at T = 0 K. Furthermore, we evaluated eqs , (), (), and () based on the quasi-harmonic approximation (QHA).…”
mentioning
confidence: 99%